Analysis of the effect of rock salt on grout's freeze-thaw strength with the Taguchi Method - Zaimoğlu, Ahmet Şahin; Ayık Kılıç, Elif; Artuk, Fatih (Polar Science, 2022)
Grouting is the injection of mixtures with high pressure into the voids, cracks, or pores that may exist in the soil. In the case of rock salt being present in the formations where the grouting is performed, studies on the effects of this salt presence on the freeze-thaw strength of the grout are rare in the literature. The Taguchi Method was used to assess the effect of rock salt on the freeze-thaw strength of grouts in this research (at 0, 50, and 100 freeze-thaw cycles). For the experimental design, a 3-parameter and a 4-level experimental design table were employed following the Taguchi Method. In the Taguchi Method, water/cement ratio (W/C), sand percentage (SP), and saturation percentage with rock salt (SPRS) were chosen as experimental parameters. The levels of these parameters were determined as 0.8-1.0-1.2-1.4; 0%-25%-50%–100%; and 0%-25%-50%–100%, respectively. The freeze-thaw strength of the prepared grout samples at 0, 50, and 100 cycles were determined. As a result of the experiments, it was determined that the strength of 50 cycles of grout samples increased by up to the 2nd level (25%) of SPRS. The 0 and 100 freeze-thaw strength decreased with the increase in SPRS. Pertaining to all prepared grout samples, freeze-thaw strength decreased when W/C increased and rose as SP increased in general. journal article